Design of a fuzzy controller using a genetic algorithm for stator flux estimation - Karakose, M; Kaya, M; Akin, E (Springer-Verlag Berlin, 2001)
Performance of the field orientation in induction motors depends on the accurate estimation of the flux vector. The voltage model used for field orientation has in the flux calculation process an open integration problem, which is generally solved with a feedback loop. In this paper, a new method is developed for the feedback loop of the integrator. The method, as apart from studies in the literature, uses a fuzzy controller determined membership functions using a genetic algorithm (GA). For this purpose, a fuzzy controller is designed and tested on various motors of different power ratings. The proposed method is simulated by using MATLAB-SIMULINK and implemented on an experimental system using a TMS320C31 digital signal processor.
International Conference on Computational Science (ICCS 2001) -- MAY 28-30, 2001 -- San Francisco, CA
Keywords: Induction-Motor